Acetic acid-modified zinc oxide nanoparticles for solid phase extraction of Cu(II) and Cr(III) in water. Issue 1 (2nd January 2022) - Tesfaye, Asnake; Amde, Meseret; Teju, Endale; Bekana, Deribachew; Megersa, Negussie
Abstract: Water pollution due to toxic metals may pose a significant effect on the environment and the biota indicating the necessity of careful management of their concentration in the system. On the other hand, a simplified and useable sample preparation technique is required for their trace analysis. In this report, a simple solid-phase extraction procedure was developed for fast extraction and preconcentration of Cu(II) and Cr(III) from waters using acetic acid modified zinc oxide nanoparticles prior to flame atomic absorption spectrometry. The extraction procedure was optimized with respect to sample volume, pH, adsorbent dose, eluent, and extraction time. Ionic strength and co-existing ions did not exhibit any significant effect on the extraction. Under optimum conditions, with an enrichment factor of 40 and recoveries of over 95%, the limits of detection for both analytes were in the low µg L −1 range. Intra-day and inter-day precision were at about 3% to 4%. The method was applied for trace determination of the analytes in real water samples.